ESTIMATION OF GENETIC DIVERSITY IN SILVER CATFISH (Chrysicthys nigrodigitatus) USING RANDOM AMPLIFIED POLYMORPHIC DNA - Akpomughe , Emuesiri; Nwachi, O. F.; Awhefeada, O. K. (FUDMA JOURNAL OF SCIENCES, 2024)
The Silver catfish (Chrysicthys nigrodigitatus) is widely distributed along River Niger.This study was carried out to characterize Silver Catfish found along River Niger, with the help of morphometric and random amplified polymorphic DNA for genetic analysis to determine variation in strain that can be used for identification of the strains and possible allocation. Samples were collected from three stations, namely; Illushi, Illah and Onitsha and total of 1 50 samples (50 each) of silver catfish was collected from landing station. Where 12% of the total sampled fish was used for genetic analysis and 100% of the sample was used for morphometric analysis. Result obtain from the morphometric analysis along River Niger show that dorsal fin length and head length with a value of 0.749 and 0.230 respectively are significantly different (p<0.05) in the sample fish can be used for identification. Result obtained for genetic analysis indicate that samples from the three locations are positively correlated. Value between Illah and Illushi is 0.8991 with a percentage variation of 80%; Onitsha and Illah with a correlated value of 0.79045, a variation of 63% and Onitsha and Illushi with a correlated value of 0.76354 a percentage variation of 50%. Dendogram, Darwin’s hierarchy and Darwin’s radii graph from the study also show that species are from one ancestry. Identification of species for domestication purpose can use morphometric features. Inline breeding between strains in these locations may be necessary to improve strains because of correlation of samples.